A geospatially-enabled web tool for urban water demand forecasting and assessment of alternative urban water management strategies. (November 2017) - Sharvelle, Sybil; Dozier, Andre; Arabi, Mazdak; Reichel, Brad
Abstract: This study develops and demonstrates the Integrated Urban Water Model (IUWM) for forecasting urban water demand with options to assess effects of water conservation and reuse. While water and energy balance drive hydrologic, storage and recycling simulations on a daily timestep, social and infrastructural processes are resolved by spatially distributed parameters. IUWM is deployed as an online tool with geographical information system (GIS) interfaces, enhancing its ease of use and applicability at building to municipal scales. The performance of the model at varying spatial scales was evaluated with extensive water metering data for the City of Fort Collins, Colorado. The calibrated model provided very good estimates of demands at individual block group as well as the municipal service area. The capacity of IUWM for the assessment of the spatiotemporal variability of water consumption and effects of water demand management strategies under climate and urban growth scenarios is discussed. Highlights: An urban water demand forecasting model called IUWM is developed with options for assessing impact from water conservation and reuse strategies. IUWM is deployed as a platform independent web tool that can be accessed from commonly-used web browsers. IUWM includes a GIS interface to enable geospatial mapping with components to access readily available data from public data warehouses. IUWM can be reliably used to estimate indoor and outdoor water use. Results show the applicability of IUWM to assess demand management strategies under climate change, population growth and land use change.